2019
DOI: 10.5703/1288284316919
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Cost Analysis for Short- and Medium-Span Bridges

Abstract: Life-cycle cost analysis (LCCA) has been defined as a method to assess the total cost of a project. It is a simple tool to use when a single project has different alternatives that fulfill the original requirements. Different alternatives could differ in initial investment, operational and maintenance costs among other long term costs. The cost involved in building a bridge depends upon many different factors. However, long-term cost need to be considered to estimate the overall cost of the project and determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Notably, a comprehensive LCCA conducted by Indiana Department of Transportation in 2019 on different bridge superstructures revealed that total life cycle cost of bridges is 2.5 times on an average, mainly contributed by repair, refurbishment, and replacement. 33…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, a comprehensive LCCA conducted by Indiana Department of Transportation in 2019 on different bridge superstructures revealed that total life cycle cost of bridges is 2.5 times on an average, mainly contributed by repair, refurbishment, and replacement. 33…”
Section: Methodsmentioning
confidence: 99%
“…F I G U R E 7 Lifecycle profile of a prestressed concrete I-beam bridge and deterioration curve of concrete deck for Indiana Bridge Management System. 33,34 T A B L E 5 Probabilistic estimation of whole life tCO2e of the BT-72 girder bridge superstructure. In Table 6, it is estimated that in case of the Conventional Bridge, the maximum shares of embodied carbons in permanent construction materials are constituted from the NCC (76 tons) and steel reinforcement (56 tons).…”
Section: Life Cycle Assessment Of Conventional Second Generation and ...mentioning
confidence: 99%
See 2 more Smart Citations